2017
DOI: 10.1111/ijcs.12379
|View full text |Cite
|
Sign up to set email alerts
|

Consumers’ evaluations of the efficiency of actions to improve environmental quality: A comparative study between Brazil and China

Abstract: There is a gap in our knowledge about environmentally conscious consumers in industrialized economies and the desire to achieve sustainable economies. Given that most aspects of consumer behaviour are culture bound, this paper contributes by comparing consumers' evaluations of the efficiency of actions to improve environmental quality in two of the most promising industrializing consumer societies: Brazil and China. The proposed conceptual framework includes environmental concerns, perceived consumer effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 55 publications
1
4
0
1
Order By: Relevance
“…(2017a), Mainardes, Yeh, et al. (2017b) and Wang (2014) observed that change in attitude influences purchase intention but Chowdhury and Samuel (2014) had a contradictory view. Thus, a set of mixed behavioural intentions amongst green customers poses a challenge to green manufacturers and marketers, which requires a proper investigation.…”
Section: Results From Literature Reviewmentioning
confidence: 99%
“…(2017a), Mainardes, Yeh, et al. (2017b) and Wang (2014) observed that change in attitude influences purchase intention but Chowdhury and Samuel (2014) had a contradictory view. Thus, a set of mixed behavioural intentions amongst green customers poses a challenge to green manufacturers and marketers, which requires a proper investigation.…”
Section: Results From Literature Reviewmentioning
confidence: 99%
“…The data were collected by self‐administered questionnaires. The questionnaire was prepared by collecting statements from previous studies (Papista et al, 2018; Kim, 2017; Mainardes et al, 2017) and some statements were developed for this study. A pilot study was conducted and based on that the survey instrument was modified.…”
Section: Methodsmentioning
confidence: 99%
“…External Motivators (EM), in turn, include marketing messages, whose goal is to improve awareness of environment weaknesses, as well as advertising of green products and institutional commitment, cause-related marketing, educational campaigns sponsored by government, and the availability of recycling centers and collection points (Mainardes et al, 2017).…”
Section: Proposed Modelmentioning
confidence: 99%
“…Os motivadores externos incluem mensagens de marketing que têm como objetivo melhorar a conscientização das fraquezas ambientais, bem como a publicidade de produtos verdes, o compromisso institucional, o marketing relacionado a causas, campanhas educacionais patrocinadas pelo governo, além da disponibilidade de centros de reciclagem e de coleta (Mainardes, Yeh & Leal, 2017).…”
Section: Modelo Propostounclassified